PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS PADA TAMAN REKREASI WONDERIA SEMARANG) - Panjaitan, Virginia Meryanta; Suryoko, Sri (Jurnal Ilmu Administrasi Bisnis, 2017)
The tourism sector is one sector which has bright prospects and huge potential for development. Humans are increasingly recognizing the importance of entertainment to release saturation and refresh your mind. Wonderia recreational park is an object Travel Semarang in Semarang City, which is one means of entertainment and recreation for menyedikan modern conceptual entertainment facilities, recreational and community activities. Recreational park Wonderia Semarang included into the top five most favored tourist attraction by tourists, but in the last 5 years Wonderia Semarang recreation park has begun rarely visited.The purpose of this study was to determine the effect of price and quality of service on purchasing decisions in the recreation park Wonderia Semarang. This type of research is explanatory research, with a sample of 100 respondents who visited Wonderia and decision maker. Sampling technique used is accidental sampling and purposive sampling. Research results obtained by analyzing primary data using validity, reliability test, correlation coefficient, determination coefficient, simple linear regression analysis and tests of significance in both directions.Most respondents (43%) stated the price is quite cheap. Most respondents (55%) stated that the quality of service is good. The results of this study indicate that there is a strong relationship between the variables in the category of price and quality of service with the purchase decision where the r value of 0.733. Both independent variables proved to have a positive and significant impact on purchasing decisions. Evidenced by the results of test calculations positive regression coefficient of 0.250 to 0.208 for the price and quality of service. F-count value amounted to 56.299 larger than F-table (3.090). If partially tested, the more influence purchasing decisions is the variable quality of service. However, when tested together more influential is the price variable.Suggested recreation park owner Wonderia Semarang provide efficient package vehicle to play and improve the quality of services provided, such as understanding Wonderia SOP to employees as well as the treatment of physical conditions and locations of games in Wonderia.